Method for improving fineness of laser activation selective metallization fine line

By covering the surface of the workpiece with a hydrostatic layer before laser activation and performing laser activation and chemical plating in a hydrostatic medium, the problem of large width of metal fine lines in the existing technology is solved, and higher precision and lower cost metal circuit preparation is achieved, which has broad application prospects.

CN120591765APending Publication Date: 2025-09-05SICHUAN UNIV

Patent Information

Application Number
CN202510776343.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-11
Publication Date
2025-09-05

AI Technical Summary

Technical Problem

The existing laser-activated selective metallization process obtains a large metal line width in an air medium, which limits the size and precision of the metal circuit and makes it difficult to meet the needs of high-precision and miniaturized integration.

Method used

Before laser activation, a hydrostatic layer is covered on the surface of the workpiece to be activated, and the hydrostatic layer is used as a medium for laser activation. A laser activation pattern is formed in the hydrostatic medium, and then chemical plating is performed to prepare a metal pattern.

Benefits of technology

It significantly reduces the line width of metal wires, improves the fineness and integration capability of metal circuits, simplifies process steps, reduces costs, and is suitable for large-scale industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a method for improving the fineness of a laser activation selective metallization fine line by using a water layer. The invention belongs to the field of laser activation selective metallization, and particularly relates to a method for improving the fineness of a metal layer through a water layer in the laser activation selective metallization machining process. The inventor finds that the surface of the selective metallization composite material capable of being activated by laser is covered with a horizontal hydrostatic layer, so that activated thin wires with the fineness degree superior to the line width limit in an air medium can be activated on the composite material containing a laser sensitizer by laser, and chemical copper plating with a good effect can be carried out on the surface of an activated area. The metal fine wire with the wire width of 55-60 microns is obtained by covering the composite material base material with the horizontal static water layer. Compared with a traditional air medium processing method, the method breaks through the limit of coating fineness of laser selective activation processing under an air medium, and the obtained coating is very excellent in thickness and strength. The method has the advantages of low cost, convenience in manufacturing, easiness in large-scale use and excellent industrial application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for improving the fineness of laser-activated selective metallization fine lines. Background Art

[0002] Laser Activated Selective Metallization (LISM) uses a computer to control the laser's processing trajectory according to the trajectory of the conductive pattern. The laser is projected onto the formed three-dimensional device to be processed. In a very short time, the processing pattern is selectively activated. The activated surface is then electrolessly plated, depositing metals such as copper, nickel, or gold in the activated area to form conductive circuits. This process not only enables highly flexible production but also makes ultra-fine circuit manufacturing and micro-assembly possible.

[0003] Laser activated selective metallization technology has the advantages of high production efficiency, low cost, small product size, flexible design, and high conductivity of the metal layer obtained by chemical plating. When there is a design requirement to change the circuit pattern, it is only necessary to redesign the circuit pattern through a computer without the need to design and manufacture a mask. Compared with traditional selective metallization methods, laser induced activation selective metallization methods have the characteristics of flexible design, short production cycle, and suitability for large-scale production. At this stage, it has been widely used in communications, medical equipment, motors and precision machinery, automobiles and aerospace, electronic equipment and other fields. With the rapid popularization and development of 5G communications, traditional FRPC antennas and PDS antennas can no longer meet the performance requirements of 5G mobile phones. Almost all smartphones are currently using LISM antennas.

[0004] The laser-activated selective metallization process typically involves first activating the surface of a workpiece with a laser, then depositing a metal layer in the laser-activated area via chemical plating to create the desired metal circuits and patterns. However, existing laser activation processes typically achieve etched activation linewidths significantly larger than the laser spot diameter. The large metal line widths achieved by laser-activated selective metallization in air limit the size, precision, and miniaturization of metal circuits designed and fabricated using LISM.

[0005] The methods currently reported to improve the fineness of laser activated selective metallization fine lines are mainly the following:

[0006] 1. Optimize laser parameters

[0007] Adjusting the laser wavelength: Selecting the appropriate laser wavelength is crucial to improving precision. For example, when MoO3 is used as a laser activator, the maximum width of copper wires prepared using a 1064nm near-infrared laser can be as narrow as 78.1μm (Autocatalytic Laser Activator of Ultraviolet and Near-Infrared Lasers: Fabrication of Circuits on Polymer Substrates by Selective Metallization, DOI: 10.1021 / acsami.2c06855). However, the precision limit explored by adjusting various laser parameters is limited by the basic conditions of the laser. Based on this, this method controls parameters such as laser power, scanning speed, and laser frequency, and combines them with a covering hydrostatic layer to process in a hydrostatic medium under multiple laser parameters, further reducing the maximum line width to 55-60μm and improving the precision of the metallized fine lines.

[0008] 2. Improve activators and coatings

[0009] Develop new activators: Use activators with higher activity and selectivity, such as MoO3, which partially converts Mo into 6+ Reduced to Mo 5+ , resulting in an increase in oxygen vacancies and increased activity, thereby improving the fineness of the metallized fine lines. In addition, a tungsten-containing sensitizing aid is also an option. It can be applied to a variety of laser wavelengths and has excellent laser activation effects (such as patent application number: CN202111183962.1, invention name: Application of tungsten-containing sensitizing aids in the preparation of laser-activated selectively metallized resin compositions). However, the fineness limit obtained by this method through the development of new laser sensitizers is limited by the basic conditions of the laser. This method further explores the combination of multiple laser sensitizers and polymers, including MoO3, and confirms that after the surface is covered with a hydrostatic layer, the metal fine line limit width can be further reduced and the fineness can be improved.

[0010] Using a hydrophobic coating to assist: Coating a hydrophobic coating on the substrate surface and then controlling the hydrophilic / hydrophobic properties of the substrate surface through laser selective etching can improve the wetting selectivity of the precursor solution and avoid the "overflow plating" problem caused by the activation solution flowing into the pores, thereby increasing the resolution of the deposited copper lines to 60μm (Wu Liexin, et al., A hydrophobic coating-assisted hybrid additive manufacturing of high-precision PEEK-based three-dimensional electronics, DOI: 10.1088 / 2631-7990 / acd826). However, the above-mentioned method of using a hydrophobic coating requires adding a coating and controlling the hydrophilic / hydrophobic properties to achieve the target resolution line width. The process steps are cumbersome, the operation is complex, and the cost is high.

[0011] Optimizing the coating preparation process: Controlling the coating's thickness and uniformity. For example, applying the coating to the substrate surface by brushing or spraying to form a film with an average thickness of 47 μm ensures uniformity and consistency during laser activation and electroless plating (Zhan Zhenxiang, Preparation of a Novel Laser-Induced Coating for Selective Metallization, Powder Metallurgy Materials Science and Engineering, Issue 6, 2017). However, this optimized preparation method requires applying the coating and controlling the coating thickness to achieve the desired resolution linewidth. This process is cumbersome, complex, and costly.

[0012] 3. Improve substrate surface treatment

[0013] Pretreatment process: Before laser processing, the substrate is pretreated, such as soaking in chemicals, coating with a thin film or plasma treatment, which can form an activator-repellent layer on the surface of the substrate to reduce or prevent the adsorption of the activator, thereby improving selectivity.

[0014] Laser processing depth and roughness control: By precisely controlling the laser processing depth and surface roughness, the bonding strength between the graphic part and the metal layer can be improved, while avoiding uneven metallization caused by an overly rough surface. However, this method requires pre-treatment such as soaking in special chemicals, which is costly, cumbersome, and requires complex post-processing using chemicals.

[0015] 4. Optimize the chemical plating process

[0016] Strict control of electroless plating bath parameters: The activity, plating start speed, and deposition rate of the electroless plating bath significantly influence the fineness of the metallization. Precise control of bath composition, temperature, pH, and other parameters is required to ensure that metal ions crystallize and deposit only in areas with active centers, avoiding overflow or missed plating. However, this method places stringent requirements on the composition and operating parameters of the electroless plating bath, requiring stringent conditions.

[0017] A multi-step electroless plating process—first performing a thin layer of electroless plating to form a uniform metal layer followed by subsequent thickening—can improve the fineness and uniformity of metallized lines. However, this method requires repeated subsequent treatment of the metal layer, resulting in complex steps, strict parameter control, and high costs.

[0018] 5. Composite additive manufacturing technology

[0019] Combining laser-activated metallization with other additive manufacturing technologies, such as fused deposition modeling (FDM), can achieve more complex three-dimensional conformal electronics manufacturing and further improve the fineness of metallized lines by optimizing composite process parameters. However, the fineness limit explored by adjusting various laser parameters is limited by the basic conditions of the laser, and it is impossible to obtain fine metallized lines with a fineness superior to that achieved by processing in traditional media. This does not break through the limitations of the process itself, and the cost is high and the scope of application is limited.

[0020] In summary, compared with the method of the present invention, the currently used methods have great room for improvement in breaking through the basic limitations of lasers, complex preprocessing, strict parameter control requirements, high cost, complex post-processing, and tedious post-processing.

[0021] With the development of the times, the application and development prospects of traditional electronic devices have been seriously hindered by problems such as low circuit integration efficiency, low integration precision, and substrate waste. To meet the requirements of flexible, lightweight, and miniaturized instruments and equipment, the exploration of low-cost, high-efficiency integration of high-precision metal circuits and metal patterns has gradually attracted people's attention. Summary of the Invention

[0022] In order to overcome the problem of limited processing width of metal fine lines obtained by conventional laser activated selective metallization in air medium, the present invention aims to provide a method for obtaining finer metal line width.

[0023] The present invention provides a method for improving the fineness of laser-activated selective metallization lines. Prior to laser activation, a hydrostatic layer is applied to the surface of the workpiece or template to be activated. The hydrostatic layer is defined herein as an artificially covered layer of water that is free of flow, disturbance, and maintains a horizontal surface throughout the entire processing process. The hydrostatic layer can form on the template surface due to tension. This formation is only driven by tension when the water layer is too thin. However, when the water layer is sufficiently thick (e.g., greater than 0.5 mm), a stable hydrostatic layer can be formed without the need for surface tension.

[0024] The hydrostatic layer is water with a thickness of 0.5 to 10 mm, preferably 1.0 to 5 mm.

[0025] Specifically, it includes the following steps:

[0026] Step 1: forming the laser-activatable selective metallization composite material into a part or a prototype;

[0027] Step 2: Place the above-mentioned workpiece or sample in a container filled with water so that the upper surface of the workpiece or sample is covered with a static water layer;

[0028] Step 3: Use laser to directly activate the upper surface of the workpiece or sample in a static water medium to form a laser activation pattern;

[0029] Step 4: After cleaning the workpiece or sample activated by laser in step 3, perform chemical plating to deposit metal patterns or metal circuits in the laser activated area.

[0030] The laser-activatable selective metallized composite material in step 1 is prepared from a laser sensitizer and a polymer, and the laser sensitizer accounts for 0.1 wt.% to 20 wt.% of the total mass of the composite material;

[0031] The polymer is selected from any one of acrylonitrile-butadiene-styrene copolymer, polycarbonate, styrene-acrylonitrile copolymer, polypropylene, polyethylene, polyethylene terephthalate, polybutylene terephthalate, polyamide, polystyrene, polyoxymethylene, polyacrylate, polyvinyl chloride, K resin, ethylene-acrylate copolymer, ethylene-vinyl acetate copolymer, ASA, PEN, polyphenylene ether, polyphenylene sulfide, polyetheretherketone, polyurethane, nylon elastomer, SEBS, SEPS, SEEPS, polyester elastomer, POE, or a mixture of two or more thereof;

[0032] The laser sensitizer is selected from any one of copper salts, copper oxides, copper hydroxides, organic copper complexes, chromium salts, chromium oxides, chromium hydroxides, manganese salts, manganese oxides, manganese hydroxides, iron salts, iron oxides, iron hydroxides, molybdenum salts, molybdenum oxides, molybdenum hydroxides, aluminum salts, aluminum oxides, aluminum hydroxides, bismuth salts, bismuth oxides, bismuth hydroxides, tin salts, tin oxides, tin hydroxides, antimony salts, antimony oxides, antimony hydroxides, zinc salts, zinc oxides, zinc hydroxides, tungsten salts, tungsten oxides, tungstic acid, neodymium salts, neodymium oxides, neodymium hydroxides, terbium salts, terbium oxides, terbium hydroxides, lanthanum salts, lanthanum oxides, lanthanum hydroxides, niobium salts, niobium oxides, niobium hydroxides, or a mixture of two or more thereof;

[0033] The metal is a conductive metal; preferably, the conductive metal is selected from copper, gold, chromium or nickel.

[0034] Preferably, the laser sensitizer accounts for 1.0wt.% to 10wt.% of the total mass of the composite material.

[0035] Wherein, in step 3, the wavelength of the laser-activated near-infrared laser is 500-1100 nm, the laser power is 0.5-20 W, the laser scanning rate is 500-3000 mm / s, and the laser frequency is 10-300 kHz; the irradiated medium is a static water layer, and the plating method is chemical plating deposition; preferably, the laser wavelength is 532 nm, 808 nm or 1064 nm, the laser power is 1.0 W to 11 W, the laser scanning speed is 1000-2000 mm / s, and the laser frequency is 20-220 kHz;

[0036] In step 4, the metal pattern includes a circuit, a decorative pattern or a graphic.

[0037] The present invention also provides a fine metal pattern prepared by the method for improving the fineness of laser activated selective metallization fine lines.

[0038] The present invention provides a decorative object, component or electronic device comprising the fine metal pattern.

[0039] Compared with the prior art, the method provided by the present invention has the following beneficial effects:

[0040] (1) The method of the present invention does not require the manufacture of a mask, and the pattern can be freely designed through software. For example, to prepare flexible liquid metal patterns with different patterns, it is only necessary to change the pattern to be printed in the laser control software. Compared with traditional methods that require the manufacture of masks (such as lithography, microfluidic injection, etc.), the method of the present invention has good production flexibility, simple operation, controllable costs, and has the prospect of large-scale industrial application.

[0041] (2) The method of the present invention does not require the use of expensive equipment, and the laser used is low in cost.

[0042] (3) The static water layer used in the method of the present invention can isolate and absorb the odorous gases during processing.

[0043] (4) The fineness of the metal wires prepared by the method of the present invention is significantly better than that of the metal wires prepared in the air medium.

[0044] (5) The refined metal layer prepared by the method of the present invention is neatly arranged and plays an important role in the fields of high-efficiency integrated circuits and the manufacture of refined electronic components, and has a very broad application prospect.

[0045] The present invention utilizes a hydrostatic layer to cover a composite material, and then performs laser activation and metallization to obtain metal wires with enhanced fineness and reduced line width. The metal wires can be designed and integrated into smaller and more precise components. Therefore, the metal wires have broad practical application value and application prospects in the miniaturization of application devices and the refinement of integrated circuits.

[0046] Based on the above contents of the present invention, according to common technical knowledge and customary means in this field, without departing from the above basic technical ideas of the present invention, other various forms of modifications, replacements or changes can be made.

[0047] The following further describes the above content of the present invention in detail through specific embodiments in the form of examples. However, this should not be construed as limiting the scope of the above subject matter of the present invention to the following examples. All technologies implemented based on the above content of the present invention fall within the scope of the present invention. DETAILED DESCRIPTION

[0048] The raw materials and equipment used in the specific embodiments of the present invention are all known products and are obtained by purchasing commercial products.

[0049] (1) The equipment information used in the present invention is as follows:

[0050] Twin-screw extruder, screw diameter 35 mm, screw length-diameter ratio 36:1, produced by Nanjing Jieente Electromechanical Co., Ltd.

[0051] Injection molding machine, model MA600, manufactured by Haitian Machinery Co., Ltd.;

[0052] Laser marking machine, model MF-EA, fiber pulse laser marking machine, maximum laser power 20W, laser wavelength 1064nm.

[0053] Laser marking machine, model BOT808-1000DT, fiber pulse laser marking machine, laser maximum power 7W, laser wavelength 808nm.

[0054] Laser marking machine, model MF-HH, fiber pulse laser marking machine, laser maximum power 10W, laser wavelength 532nm.

[0055] (2) The specific information of the base polymer used to prepare the standard sample of the present invention is as follows:

[0056] Acrylonitrile butadiene styrene (ABS): Chimei, PA757 (density: 1.05g / cm 3 ; Melt flow rate: 1.8g / 10min, 200℃, 5Kg).

[0057] Polypropylene: Daqing Petrochemical, T30S (density: 0.9g / cm 3 ; Melting temperature: 189°C).

[0058] Polystyrene: Duzishan Petrochemical, GPPS-500 (density: 1.04g / cm 3 ; Melt flow rate: 5g / 10min, 200℃, 5Kg; Heat deformation temperature: 89℃).

[0059] Polycarbonate: General Electric, PC121R (density: 1.2g / cm 3 ; Melt flow rate: 17.5g / 10min, 300℃, 1.2Kg; Heat deformation temperature: 125℃).

[0060] Polyethylene terephthalate: Far Eastern Textile Industry, CB-602 (density: 1.40 g / cm 3 ; Melting temperature: 245°C).

[0061] Polyethylene terephthalate: BASF, Germany, PBTB4500 (density: 1.3g / cm 3 ; Melting temperature: 230℃.

[0062] SEBS: Japan Kuraray, HYBRA7311F (density: 0.89g / cm 3 ; melting temperature 200°C).

[0063] Polyamide 66: Lanxess, Germany, A30S (density: 1.14g / cm 3 ; Melting temperature: 260°C).

[0064] Example 1

[0065] First, 99 g of acrylonitrile-butadiene-styrene (ABS) resin and 1.0 g of basic copper phosphate powder, a laser sensitization aid, were thoroughly mixed in a high-speed mixer for 3 minutes. Then, the mixed material was melt-extruded and granulated in a twin-screw extruder at an extrusion temperature of 190°C to obtain a composite material that can be laser-activated and selectively metallized.

[0066] Then, the prepared laser-activated selectively metallized composite material is injection molded into a plastic sheet by an injection molding machine at an injection molding temperature of 190°C.

[0067] The plastic sheet was laser activated using the following conditions: a pulsed near-infrared laser with a laser wavelength of 1064 nm, a laser energy of 3 W, a laser frequency of 40 kHz, and a water layer thickness of 1 mm.

[0068] According to the laser-activated selective metallized composite material chemical plating method and process known in the art, the plastic sheet after laser activation was chemically copper-plated. The chemical copper plating used a reduction system with formaldehyde as the reducing agent and copper sulfate as the metallic copper salt. The composite material was placed in a 50°C chemical copper plating solution and reacted for 100 minutes. Air was continuously introduced for stirring to ensure the uniformity of the copper layer.

[0069] After the electroless copper plating is completed, a thin copper layer is formed on the surface of the composite material in the laser-activated area. The surface copper lines are observed using optical microscopy and scanning electron microscopy.

[0070] When the thickness of the water layer is between 1 and 5 mm, the width of the fine lines in the metal layer is between 55 and 60 microns.

[0071] The test results are shown in Table 1.

[0072] Example 2

[0073] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1. The only differences were the matrix polymer and laser sensitization agent used: 95 g of ABS resin and 5 g of basic copper phosphate powder. The laser wavelength was 1064 nm, the laser power was 3 W, the laser frequency was 40 kHz, and the water layer thickness was 1 mm. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0074] The test method is the same as that in Example 1. The test results are shown in Table 1.

[0075] Example 3

[0076] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1. The only differences were the matrix polymer and laser sensitization agent used: 90 g of ABS resin and 10 g of basic copper phosphate powder. The laser wavelength was 1064 nm, the laser power was 3 W, the laser frequency was 40 kHz, and the water layer thickness was 1 mm. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0077] The test method is the same as that in Example 1. The test results are shown in Table 1.

[0078] Example 4

[0079] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1. The only differences were the matrix polymer and laser sensitization agent used: 80 g of ABS resin and 20 g of basic copper phosphate powder. The laser wavelength was 1064 nm, the laser power was 2 W, the laser frequency was 40 kHz, and the water layer thickness was 1 mm. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0080] The test method is the same as that in Example 1. The test results are shown in Table 1.

[0081] Example 5

[0082] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1. The only differences were the matrix polymer and laser sensitization agent used: 80 g of ABS resin and 20 g of basic copper phosphate powder. The laser wavelength was 1064 nm, the laser power was 2 W, the laser frequency was 40 kHz, and the water layer thickness was 3 mm. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0083] The test method is the same as that in Example 1. The test results are shown in Table 1.

[0084] Example 6

[0085] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1. The only differences were the matrix polymer and laser sensitization agent used: 80 g of ABS resin and 20 g of basic copper phosphate powder. The laser wavelength was 1064 nm, the laser power was 2 W, the laser frequency was 40 kHz, and the water layer thickness was 5 mm. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0086] The test method is the same as that in Example 1. The test results are shown in Table 1.

[0087] Example 7

[0088] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1. The only differences were the base polymer and laser sensitization agent used: 99 g of polystyrene resin and 1 g of copper-chromium oxide powder. The laser wavelength, power, and frequency were 808 nm, 5 W, and 80 kHz, respectively. The water layer thickness was 1 mm. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0089] The test method is the same as that in Example 1. The test results are shown in Table 1.

[0090] Example 8

[0091] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1. The only differences were the base polymer and the laser sensitizer used: 95 g of polystyrene resin and 5 g of copper-chromium oxide powder. The laser wavelength, power, and frequency were 808 nm, 5 W, and 80 kHz, respectively. The water layer thickness was 1 mm. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0092] The test method is the same as that in Example 1. The test results are shown in Table 1.

[0093] Example 9

[0094] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1, with the following differences: 90 g of polystyrene resin and 10 g of copper-chromium oxide powder as the base polymer and laser sensitizer. The laser wavelength was 808 nm, the power was 5 W, the frequency was 80 kHz, and the water layer thickness was 1 mm. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0095] The test method is the same as that in Example 1. The test results are shown in Table 1.

[0096] Example 10

[0097] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1. The only differences were the base polymer and the laser sensitizer used: 80 g of polystyrene resin and 20 g of copper-chromium oxide powder. The laser wavelength, power, and frequency were 808 nm, 5 W, and 80 kHz, respectively. The water layer thickness was 1 mm. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0098] The test method is the same as that in Example 1. The test results are shown in Table 1.

[0099] Example 11

[0100] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1. The only differences were the base polymer and the laser sensitizer used: 80 g of polystyrene resin and 20 g of copper-chromium oxide powder. The laser wavelength was 1064 nm, the power was 5 W, the frequency was 80 kHz, and the water layer thickness was 3 mm. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0101] The test method is the same as that in Example 1. The test results are shown in Table 1.

[0102] Example 12

[0103] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1. The only differences were the base polymer and the laser sensitizer used: 80 g of polystyrene resin and 20 g of copper-chromium oxide powder. The laser wavelength was 1064 nm, the power was 5 W, the frequency was 80 kHz, and the water layer thickness was 5 mm. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0104] The test method is the same as that in Example 1. The test results are shown in Table 1.

[0105] Example 13

[0106] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1. The only differences were the base polymer and laser sensitizer used: 99g of polyamide 66 resin and 1g of molybdenum trioxide powder. The laser wavelength was 1064nm, the power was 3W, the frequency was 80kHz, and the water layer thickness was 1mm. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0107] The test method is the same as that in Example 1. The test results are shown in Table 1.

[0108] Example 14

[0109] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1. The only differences were the base polymer and laser sensitizer used: 95 g of polyamide 66 resin and 5 g of molybdenum trioxide powder. The laser wavelength was 1064 nm, the power was 3 W, the frequency was 80 kHz, and the water layer thickness was 1 mm. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0110] The test method is the same as that in Example 1. The test results are shown in Table 1.

[0111] Example 15

[0112] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1. The only differences were the base polymer and laser sensitizer used: 90 g of polyamide 66 resin and 10 g of molybdenum trioxide powder. The laser wavelength was 1064 nm, the power was 3 W, the frequency was 80 kHz, and the water layer thickness was 1 mm. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0113] The test method is the same as that in Example 1. The test results are shown in Table 1.

[0114] Example 16

[0115] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1. The only differences were the base polymer and laser sensitizer used: 80 g of polyamide 66 resin and 20 g of molybdenum trioxide powder. The laser wavelength was 1064 nm, the power was 3 W, the frequency was 80 kHz, and the water layer thickness was 1 mm. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0116] The test method is the same as that in Example 1. The test results are shown in Table 1.

[0117] Example 17

[0118] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1. The only differences were the base polymer and laser sensitizer used: 80 g of polyamide 66 resin and 20 g of molybdenum trioxide powder. The laser wavelength was 1064 nm, the power was 3 W, the frequency was 80 kHz, and the water layer thickness was 3 mm. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0119] The test method is the same as that in Example 1. The test results are shown in Table 1.

[0120] Example 18

[0121] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1, with the following differences: 80 g of polyamide 66 resin and 20 g of molybdenum trioxide powder as the base polymer and laser sensitizer. The laser wavelength was 1064 nm, the power was 3 W, the frequency was 80 kHz, and the water layer thickness was 5 mm. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0122] The test method is the same as that in Example 1. The test results are shown in Table 1.

[0123] Example 19

[0124] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1. The only differences were the matrix polymer and laser sensitizer used: 95g of polyethylene terephthalate resin and 5g of antimony tin oxide powder. The laser wavelength, power, and frequency were 808nm, 9W, and 100kHz, respectively. The water layer thickness was 1mm. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0125] The test method is the same as that in Example 1. The test results are shown in Table 1.

[0126] Example 20

[0127] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1. The only differences were the matrix polymer and laser sensitizer used: 95g of polyethylene terephthalate resin and 5g of antimony tin oxide powder. The laser wavelength, power, and frequency were 808nm, 9W, and 100kHz, respectively. The water layer thickness was 3mm. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0128] The test method is the same as that in Example 1. The test results are shown in Table 1.

[0129] Example 21

[0130] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1. The only differences were the matrix polymer and laser sensitizer used: 90g of polyethylene terephthalate resin and 10g of antimony tin oxide powder. The laser wavelength, power, and frequency were 808nm, 9W, and 100kHz, respectively. The water layer thickness was 1mm. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0131] The test method is the same as that in Example 1. The test results are shown in Table 1.

[0132] Example 22

[0133] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1. The only differences were the matrix polymer and laser sensitizer used: 80g of polyethylene terephthalate resin and 20g of antimony tin oxide powder. The laser wavelength was 808nm, the power was 9W, the frequency was 100kHz, and the water layer thickness was 1mm. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0134] The test method is the same as that in Example 1. The test results are shown in Table 1.

[0135] Example 23

[0136] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared according to the method of Example 1, with the following differences: 95 g of polycarbonate resin and 5 g of terbium oxide powder as the base polymer and laser sensitizer. The laser wavelength was 1064 nm, the laser power was 9 W, the laser frequency was 100 kHz, and the water layer thickness was 3 mm. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0137] The test method is the same as that in Example 1. The test results are shown in Table 1.

[0138] Example 24

[0139] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1. The only differences were the base polymer and the laser sensitizer used: 95 g of polycarbonate resin and 5 g of terbium oxide powder. The laser wavelength was 808 nm, the laser power was 9 W, the laser frequency was 100 kHz, and the water layer thickness was 5 mm. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0140] The test method is the same as that in Example 1. The test results are shown in Table 1.

[0141] Example 25

[0142] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1. The only differences were the base polymer and laser sensitization agent used: 92 g of polycarbonate resin and 8 g of basic copper phosphate powder. The laser wavelength, power, and frequency were 532 nm, 6 W, and 240 kHz, respectively. The water layer thickness was 1 mm. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0143] The test method is the same as that in Example 1. The test results are shown in Table 1.

[0144] Example 26

[0145] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1. The only differences were the base polymer and laser sensitization agent used: 92 g of polycarbonate resin and 8 g of basic copper phosphate powder. The laser wavelength was 532 nm, the power was 6 W, the frequency was 240 kHz, and the water layer thickness was 5 mm. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0146] The test method is the same as that in Example 1. The test results are shown in Table 1.

[0147] Comparative Example 1

[0148] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1. The only differences were the matrix polymer and laser sensitization agent used: 95 g of ABS resin and 5 g of basic copper phosphate powder. The laser wavelength was 1064 nm, the power was 3 W, and the frequency was 40 kHz. Laser activation was performed in air. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0149] The test method is the same as that of Example 1, except that in all experiments of the comparative example group, no static water layer is covered on the surface of the composite material. The following comparative examples are carried out in the same manner as in Comparative Example 1. The test results are shown in Table 1.

[0150] Comparative Example 2

[0151] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1. The only differences were the matrix polymer and laser sensitization agent used: 99.2 g of ABS resin and 0.8 g of basic copper phosphate powder. The laser wavelength, power, and frequency were 1064 nm, 3 W, and 100 kHz, respectively. Laser activation was performed in air. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0152] The test method is the same as that of Comparative Example 1. The test results are shown in Table 1.

[0153] Comparative Example 3

[0154] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1. The only differences were the base polymer and the laser sensitizer used: 95 g of polystyrene resin and 5 g of copper-chromium oxide powder. The laser wavelength was 808 nm, the power was 0.5 W, and the frequency was 80 kHz. Laser activation was performed in air. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0155] The test method is the same as that of Comparative Example 1. The test results are shown in Table 1.

[0156] Comparative Example 4

[0157] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1. The only differences were the base polymer and the laser sensitizer used: 95 g of polystyrene resin and 5 g of copper-chromium oxide powder. The laser wavelength, power, and frequency were 808 nm, 1.5 W, and 80 kHz, respectively. Laser activation was performed in air. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0158] The test method is the same as that of Comparative Example 1. The test results are shown in Table 1.

[0159] Comparative Example 5

[0160] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1. The only differences were the base polymer and the laser sensitizer used: 95 g of polystyrene resin and 5 g of copper-chromium oxide powder. The laser wavelength, power, and frequency were 808 nm, 5 W, and 80 kHz, respectively. Laser activation was performed in air. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0161] The test method is the same as that of Comparative Example 1. The test results are shown in Table 1.

[0162] Comparative Example 6

[0163] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1. The only differences were the base polymer and laser sensitizer used: 95 g of polyamide 66 resin and 5 g of molybdenum trioxide powder. The laser wavelength was 1064 nm, the power was 3 W, and the frequency was 20 kHz. Laser activation was performed in air. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0164] The test method is the same as that of Comparative Example 1. The test results are shown in Table 1.

[0165] Comparative Example 7

[0166] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1. The only differences were the base polymer and laser sensitizer used: 95 g of polyamide 66 resin and 5 g of molybdenum trioxide powder. The laser wavelength was 1064 nm, the power was 3 W, and the frequency was 80 kHz. Laser activation was performed in air. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0167] The test method is the same as that of Comparative Example 1. The test results are shown in Table 1.

[0168] Comparative Example 8

[0169] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1. The only differences were the base polymer and laser sensitizer used: 95 g of polyamide 66 resin and 5 g of molybdenum trioxide powder. The laser wavelength was 1064 nm, the power was 3 W, and the frequency was 200 kHz. Laser activation was performed in air. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0170] The test method is the same as that of Comparative Example 1. The test results are shown in Table 1.

[0171] Comparative Example 9

[0172] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1. The only differences were the matrix polymer and laser sensitizer used: 95g of polyethylene terephthalate resin and 5g of antimony tin oxide powder. The laser wavelength, power, and frequency were 808nm, 9W, and 100kHz, respectively. Laser activation was performed in air. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0173] The test method is the same as that of Comparative Example 1. The test results are shown in Table 1.

[0174] Comparative Example 10

[0175] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1. The only differences were the matrix polymer and laser sensitizer used: 80g of polyethylene terephthalate resin and 20g of antimony tin oxide powder. The laser wavelength was 808nm, the power was 9W, and the frequency was 100kHz. Laser activation was performed in air. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0176] The test method is the same as that of Comparative Example 1. The test results are shown in Table 1.

[0177] Comparative Example 11

[0178] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1. The only differences were the base polymer and the laser sensitizer used: 95 g of polycarbonate resin and 5 g of terbium oxide powder. The laser wavelength was 808 nm, the power was 9 W, and the frequency was 100 kHz. Laser activation was performed in air. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0179] The test method is the same as that of Comparative Example 1. The test results are shown in Table 1.

[0180] Comparative Example 12

[0181] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1. The only differences were the base polymer and the laser sensitizer used: 95 g of polycarbonate resin and 5 g of terbium oxide powder. The laser wavelength was 1064 nm, the power was 9 W, and the frequency was 100 kHz. Laser activation was performed in air. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0182] The test method is the same as that of Comparative Example 1. The test results are shown in Table 1.

[0183] Comparative Example 13

[0184] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1. The only differences were the base polymer and the laser sensitizer used: 95g of polycarbonate resin and 5g of molybdenum trioxide powder. The laser wavelength was 1064nm, the power was 9W, and the frequency was 100kHz. Laser activation was performed in air. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0185] The test method is the same as that of Comparative Example 1. The test results are shown in Table 1.

[0186] Comparative Example 14

[0187] A laser-activated selective metallization composite material and a laser-activated plastic sheet were prepared using the same method as in Example 1. The only differences were the base polymer and laser sensitization agent used: 92g of polycarbonate resin and 8g of basic copper phosphate powder. The laser wavelength was 532nm, the power was 6W, and the frequency was 240kHz. Laser activation was performed in air. After electroless copper plating, the line width was determined using an optical microscope and a scanning electron microscope.

[0188] The test method is the same as that of Comparative Example 1. The test results are shown in Table 1.

[0189] Table 1

[0190]

[0191]

[0192]

[0193] Experimental results

[0194] In the chemical plating effect, "obvious plating" means that the metal wires are regular and the chemical plating layer is dense and without discontinuities when observed under optical and electron microscopes; "coating thickness" refers to the thickness measured under an electron microscope after the metal wire is quenched; "grid knife test" refers to the test level achieved by the coating peeling test conducted in accordance with the ASTM D3359 test standard; "limit line width" refers to the line width of fine metal wires measured under an optical microscope or electron microscope.

[0195] As can be seen from the experimental results in Table 1, Examples 1 to 26 demonstrate that the laser-activated selective metallization method using a water layer successfully directly forms metal fine wires with widths of 55 to 60 μm on various polymer surfaces at different laser sensitizer concentrations, laser powers, laser frequencies, laser wavelengths, and water layer thicknesses, achieving a significant improvement compared to the air medium.

[0196] As can be seen from the test results in Table 1, Comparative Example 1 shows that under the completely identical conditions except that the hydrostatic layer is no longer covered by the laser activation in the air medium, the ultimate line width of the metal fine line obtained on the surface of the composite material is much larger than the ultimate line width of the metal fine line obtained by laser activation and chemical plating in the hydrostatic medium.

[0197] Comparative Examples 2 to 4 show that when laser activation is carried out in an air medium and the laser sensitizer concentration is less than or equal to 0.8wt% or the laser power is less than or equal to 1.5W, the copper layer cannot be plated after laser activation. Therefore, it is impossible to obtain metal fine wires with a high degree of processing fineness in a hydrostatic medium by reducing parameters such as the laser sensitizer content and the laser power.

[0198] Comparative Examples 5 to 10 show that, under the same laser parameters, laser sensitizer type and content, polymer type and content, and combination method, except for the absence of a static water layer, the ultimate line width of the metal fine wire obtained in air is much higher than that in pure water.

[0199] Comparative Example 5 shows that under exactly the same parameters in air medium and hydrostatic medium, the ultimate line width of the metal fine wire obtained by processing in air medium is much larger than that in hydrostatic medium.

[0200] Comparative Examples 6 to 8 show that when the laser frequency is adjusted from 20 kHz to 200 kHz, the ultimate line width of the metal fine line activated by laser in air cannot reach the fineness achieved in a static water medium.

[0201] Comparative Examples 9 and 10 show that under different laser power and sensitizer contents, the ultimate line width of the metal fine line activated by laser in air cannot reach the fineness achieved in a static water medium.

[0202] Comparative Examples 11-12 show that under different laser wavelength conditions, the ultimate line width of laser-activated metal fine lines in air cannot reach the fineness achieved in a static water medium.

[0203] Comparative Examples 12-13 show that under different combinations of polymers and laser sensitizers, the ultimate line width of the metal thin line activated by laser in air cannot reach the ultimate line width of the metal thin line achieved in a static water medium.

[0204] Comparative Example 14 shows that under different combinations of polymers and laser sensitizers, the ultimate line width of the metal thin line activated by laser in air cannot reach the ultimate line width of the metal thin line achieved in a static water medium.

[0205] In summary, laser activation in air, regardless of parameter adjustment, cannot achieve the ultimate linewidth of fine metal lines achieved by laser activation in a hydrostatic layer over the composite surface. However, the hydrostatic layer over the composite surface can effectively enhance the precision of selective metallization by laser activation, enabling the production of fine metal lines with linewidths exceeding those achieved in conventional air.

[0206] The coating thickness of the composite material obtained by the method of the present invention reaches more than 2μm on multiple water layer thicknesses and multiple composite materials. The coating strength tested by a grid knife (ASTM D3359) reaches a maximum level of 5B, which is very suitable for industrial production applications. The actual application performance of the fine metal pattern obtained by processing in a static water medium is no less than that obtained by processing in an air medium.

[0207] In summary, the present invention has developed a method for using a hydrostatic layer to produce fine metal wires with a degree of fineness exceeding the fineness limit in air. The ultrafine metal layers produced by this method have great application potential in communications, medical devices, motors and precision machinery, automotive and aerospace, and electronic equipment. This method, using only the hydrostatic layer as an aid, can directly produce an ultrafine metal layer on a polymer surface after laser activation and electroless plating, eliminating the need for other complex processes. This method is low-cost, easy to manufacture, and suitable for large-scale production.

Claims

1. A method for improving the fineness of laser-activated selective metallization fine lines, characterized by: It is to cover the surface of the workpiece or sample to be activated with a static water layer before laser activation.

2. The method for improving fineness of laser activated selective metallization fine lines according to claim 1, characterized in that: The static water layer is water with a thickness of 0.5 to 10 mm.

3. The method for improving fineness of laser activated selective metallization fine lines according to claim 2, characterized in that: The thickness is 1.0 to 5 mm.

4. The method for improving fineness of laser activated selective metallization fine lines according to any one of claims 1 to 3, characterized in that: It includes the following steps: Step 1: forming the laser-activatable selective metallization composite material into a part or a prototype; Step 2: Place the above-mentioned workpiece or sample in a container filled with water so that the upper surface of the workpiece or sample is covered with a static water layer; Step 3: Use laser to directly activate the upper surface of the workpiece or sample in a static water medium to form a laser activation pattern; Step 4: After cleaning the workpiece or sample activated by laser in step 3, perform chemical plating to deposit metal patterns or metal circuits in the laser activated area.

5. The method for improving fineness of laser activated selective metallization fine lines according to claim 4, characterized in that: In step 1, the laser-activatable selective metallized composite material is prepared from a laser sensitizer and a polymer, wherein the laser sensitizer accounts for 0.1 wt.% to 20 wt.% of the total mass of the composite material; The polymer is selected from any one of acrylonitrile-butadiene-styrene copolymer, polycarbonate, styrene-acrylonitrile copolymer, polypropylene, polyethylene, polyethylene terephthalate, polybutylene terephthalate, polyamide, polystyrene, polyoxymethylene, polyacrylate, polyvinyl chloride, K resin, ethylene-acrylate copolymer, ethylene-vinyl acetate copolymer, ASA, PEN, polyphenylene ether, polyphenylene sulfide, polyetheretherketone, polyurethane, nylon elastomer, SEBS, SEPS, SEEPS, polyester elastomer, POE, or a mixture of two or more thereof; The laser sensitizer is selected from any one of copper salts, copper oxides, copper hydroxides, organic copper complexes, chromium salts, chromium oxides, chromium hydroxides, manganese salts, manganese oxides, manganese hydroxides, iron salts, iron oxides, iron hydroxides, molybdenum salts, molybdenum oxides, molybdenum hydroxides, aluminum salts, aluminum oxides, aluminum hydroxides, bismuth salts, bismuth oxides, bismuth hydroxides, tin salts, tin oxides, tin hydroxides, antimony salts, antimony oxides, antimony hydroxides, zinc salts, zinc oxides, zinc hydroxides, tungsten salts, tungsten oxides, tungstic acid, neodymium salts, neodymium oxides, neodymium hydroxides, terbium salts, terbium oxides, terbium hydroxides, lanthanum salts, lanthanum oxides, lanthanum hydroxides, niobium salts, niobium oxides, niobium hydroxides, or a mixture of two or more thereof; The metal is a conductive metal; preferably, the conductive metal is selected from copper, gold, chromium or nickel.

6. The method for improving fineness of laser activated selective metallization fine lines according to claim 5, characterized in that: The laser sensitizer accounts for 1.0 wt.% to 10 wt.% of the total mass of the composite material.

7. The method for improving fineness of laser activated selective metallization fine lines according to claim 4, characterized in that: In step 3, the wavelength of the laser-activated near-infrared laser is 500-1100 nm, the laser power is 0.5-20 W, the laser scanning rate is 500-3000 mm / s, and the laser frequency is 10-300 kHz; the irradiated medium is a static water layer, and the plating method is chemical plating deposition; preferably, the laser wavelength is 532 nm, 808 nm or 1064 nm, the laser power is 1.0 W to 11 W, the laser scanning speed is 1000-2000 mm / s, and the laser frequency is 20-220 kHz; In step 4, the metal pattern includes a circuit, a decorative pattern or a graphic.

8. A fine metal pattern produced by the method for improving the fineness of laser-activated selective metallization fine lines according to any one of claims 1 to 7.

9. A decorative object, component, or electronic device, characterized in that: It comprises the fine metal pattern as claimed in claim 8.

Citation Information

Patent Citations

  • Application of tungsten-containing sensitizing aid in preparation of laser-activatable selective metallized resin composition

    CN113831589A

Cited By

  • Method for improving laser activation selective metallization flatness

    CN121320928A